(The International Dimension of the Lebanese Issue (A Study in the American Role 1943 – 1990 - Mirdas, Iman Kamil (Journal of Humanities & Social Sciences, 2019)
The research focused on the international dimension of the Lebanese cause and the American role in Lebanon (1943- 90). Washington's interest in Lebanon began to increase since the 1940s following the beginning of the decline of the traditional European powers, its emergence as a new international superpower alongside the Soviet Union, the ambiguous and problematic nature of this role and the methods employed to execute it, which varied between economic aid, political alliances and military intervention. The historical and descriptively analytical approaches helped me reach the conclusion Lebanon was of great importance to the American policy to achieve its colonial interests and confront the Soviet Union, and to reduce the aggression waged by the Arabs against its ally "Israel." I have split this study into an introduction and two researches. First, the American role in Lebanon since its independence until the civil war. Second, the American role and the civil war, and the extent to which this role impacted Lebanon’s position in the regional system. I concluded the research with the most important results, including: Lebanese- American relations had many twists and turns ranging from tension to near relief, Washington considered Lebanon a trump card in the game of international power balances and as an arena to host the conflict, and ended the study with the United States of America’s undertook to support the "Israeli" entity and it defense.
Keywords: the international dimension; the Lebanese issue; the role; the American role